2016
DOI: 10.4149/bll_2016_092
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sub-chronic intraperitoneal administration of aminoguanidine on the memory and hippocampal apoptosis-related genes in diabetic rats

Abstract: Memory impairment is a common disorder in diabetes mellitus which is associated with hippocampal neuronal apoptosis. The present study was conducted to examine the effect of one-week intraperitoneal (ip), administration of aminoguanidine (AG) on passive avoidance learning (PAL) and Bcl-2 family gene expression in the hippocampus of rats. Sixty male rats were divided into ten groups: non-diabetic/diabetic animals with/without AG (50, 100, 200 and 400 mg/kg, ip) treatment for one week. PAL and Bcl-2 family genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…A recent study showed that Amg has protective effects against ovariectomy-induced memory defect and Aβ production disorder (22). Other studies have shown that one month of Amg injection improves memory by modulating Bcl-2 expression in diabetic rats (23,24). Asghari et al indicated that Amg reversed neuronal dysfunction and brain damage due to titanium dioxide and decreased the number of terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL)-positive neurons in the CA1 and other hippocampus regions (25).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that Amg has protective effects against ovariectomy-induced memory defect and Aβ production disorder (22). Other studies have shown that one month of Amg injection improves memory by modulating Bcl-2 expression in diabetic rats (23,24). Asghari et al indicated that Amg reversed neuronal dysfunction and brain damage due to titanium dioxide and decreased the number of terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL)-positive neurons in the CA1 and other hippocampus regions (25).…”
Section: Introductionmentioning
confidence: 99%